Zep Quiz in Action: Empowering Students’ Vocabulary through Gamified Learning - Rizal Wahid Permana Putra; Imam Wahyudi Karimullah; Mutmainnah Mustofa (Universitas Islam Negeri Palopo, 2025)
Gamification nowadays has emerged as powerful catalyst for transforming conventional learning into more dynamic and student-centered experience in learning vocabulary. This present study investigated the effectiveness of digital intervention using Zep Quiz, a gamified-learning platform, to empower eighth grade students’ vocabulary mastery in Indonesian EFL settings. There were 29 students at SMP Negeri Satu Atap Gondoruso 01 incorporated as the subjects. This study was a quasi-experimental design with one-group pretest-posttest design. In addition, three-meeting intervention was employed using Zep Quiz to improve students’ vocabulary mastery. The findings showed a statistically significant improvement in students’ vocabulary academic performance. The mean score increased substantially from 68.10 in pretest to 73.97 in posttest, the paired-sample t-test -7.90, p-value <0.0001, and Cohen’s d size 1.20 indicating that there was positive impact of digital intervention using Zep Quiz to promote students’ vocabulary acquisition. In addition, digital-game intervention using Zep Quiz with its interactive and gamified elements, likely creates more engaging activities, and empowers vocabulary learning. To sum up, gamified learning using Zep Quiz in language learning can be viable and effective approach to overcoming students’ challenge with limited vocabulary acquisition in Indonesian EFL settings.